2010
DOI: 10.1172/jci42686
|View full text |Cite
|
Sign up to set email alerts
|

Ectodomain shedding of EGFR ligands and TNFR1 dictates hepatocyte apoptosis during fulminant hepatitis in mice

Abstract: The cell death receptor Fas plays a role in the establishment of fulminant hepatitis, a major cause of druginduced liver failure. Fas activation elicits extrinsic apoptotic and hepatoprotective signals; however, the mechanisms by which these signals are integrated during disease are unknown. Tissue inhibitor of metalloproteinases 3 (TIMP3) controls the critical sheddase a disintegrin and metalloproteinase 17 (ADAM17) and may dictate stress signaling. Using mice and cells lacking TIMP3, ADAM17, and ADAM17-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 69 publications
7
75
0
Order By: Relevance
“…For example, a mutation in the gene encoding TNFR1 that impairs receptor shedding causes TNF receptor-associated periodic syndrome (TRAPS), an autosomal-dominant autoinf lammatory disease (18). Consistent with the findings of Rowlands et al (5), a protective role of TNFR1 shedding by TACE was also reported in TNF-α sensitization of hepatocytes to Fas-mediated death (19).…”
Section: Proinflammatory Stimuli Induce Inflammation That May Progresmentioning
confidence: 52%
“…For example, a mutation in the gene encoding TNFR1 that impairs receptor shedding causes TNF receptor-associated periodic syndrome (TRAPS), an autosomal-dominant autoinf lammatory disease (18). Consistent with the findings of Rowlands et al (5), a protective role of TNFR1 shedding by TACE was also reported in TNF-α sensitization of hepatocytes to Fas-mediated death (19).…”
Section: Proinflammatory Stimuli Induce Inflammation That May Progresmentioning
confidence: 52%
“…target in Fas-induced apoptosis in the liver (47). Our findings, however, that TIMP-3 moderates the macrophage response to apoptotic stimuli suggest that TIMP-3 is a crucial factor in determining whether proinflammatory, recruited macrophages are cleared appropriately after lung injury.…”
Section: /2mentioning
confidence: 68%
“…TIMP-3 has long been associated with apoptosis, and is generally thought to be proapoptotic. The overexpression of TIMP-3 in a number of different cell lines leads to the stabilization of cell-surface "death receptors" (Fas and TNFR), increased caspase activation, and cell death (42)(43)(44)(45)(46)(47). Although our finding that Timp3 2/2 BMDMs were resistant to sFasL-induced apoptosis supports these previous studies, we have been unable to demonstrate increased Fas shedding from Timp3 -/-cells, as might be predicted (data not shown).…”
Section: /2mentioning
confidence: 99%
“…All of these ligands contain one or more of the conserved EGF motif (CX 7 CX 4 -5 CX 10 -13 CXCX 8 GXRC, where X represents any amino acid) (7,8), but they differ in receptor specificity (9). Moreover, all ligands are synthesized as transmembrane precursors and are released by ectodomain shedding via proteolysis (10).…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%